Minimally invasive radical antegrade modular pancreatosplenectomy: routine vs. modified - Hee Joon Kim (Journal of Minimally Invasive Surgery)
Radical antegrade modular pancreatosplenectomy (RAMPS) was introduced in 2003 by Strasberg to improve survival outcomes in left-sided pancreatic ductal adenocarcinoma. Many investigators have shown the feasibility and safety of minimally invasive RAMPS (MI-RAMPS). However, the survival benefit of RAMPS is inconclusive, and possible risks following the procedure, such as exocrine and endocrine insufficiencies, cannot be ignored. Therefore, several modifications of RAMPS were designed. Modified RAMPS is not a specific technique but rather a reduced form of RAMPS that is undertaken without compromising oncologic principles. In this literature review, the surgical technique and strategies of MI-RAMPS were examined.